When Abstract and Real Learning Materials Meet in the Same Reality : Interpreting Hybrid Learning as a Solution in Christian Education - Simamora, Dame Taruli (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
Children aged 7-11 years who are in elementary school have realistic characteristics, high levels of curiosity about various things that happen around them, the spirit of learning something that will increase day by day, and difficulty understanding something that is conveyed abstractly. The learning method used by educators in elementary schools is generally face-to-face. Problems arise when required to collaborate face-to-face and online methods, both because of student boredom and because of compelling circumstances. This study aims to prove the effectiveness of hybrid learning in Christian education learning, how to maximize potential and minimize negative impacts. This research is a quantitative research, with a survey approach. Data was collected through a questionnaire, to analyze the level of student understanding after learning with hybrid learning. The population in this study was students who were in elementary school in Sipoholon North Tapanuli sub-district, with a total sample of 100 people. Sampling is done randomly in the population. Furthermore, data tabulation is carried out, and from there it is processed with the help of SPSS. Validity and reliability tests were carried out for questionnaires, and the results were analyzed for simple linear regressionThe influence of the implementation of the hybrid learning method on student understanding is 41%.